DETERMINASI PENGEMBANGAN SUMBER DAYA MANUSIA, DISIPLIN, DAN MOTIVASI TERHADAP PRODUKTIVITAS KERJA KARYAWAN PT. BARAKAH PANTAI MELAYU BATAM - Saputra, E. Kurniawan Saputra C.; Wibisono, Chablullah (Universitas Batam, 2019)
The purpose of this research was for determine of human resources development, disciplination, and motivation of employee productivity performance partially and simultaneously. The range of this research includes human resources development,disciplination,motivationandemployeeproductivity performance.This research was using quantitative data which sourced from primary data that has been collected. The population in this research were all the employees of PT Pantai Melayu Batam, as many as 58 employees, and this research was using census data as collecting data technique, which is means the total of population as many as sample data, they are 58 employees. Collecting data was using questionnaire and analyzed using regression method using SPSS software. Partial test’s results of this research showed that human resources development partially has detereminant significant to employee productivity performance in PT Pantai Melayu Batam. Disciplination partially has determinant but not significant to employee productivity performance in PT Barakah Pantai Melayu. Motivation partially has determinant but not significant to employee productivity performance. And the result of simultaneous test showed that human resources development, disciplination, and motivation simulataneously has determinant significant to employee productivity performance in PT Pantai Melayu Batam